Ultrasonographic Evaluation of Parathyroid Hyperplasia in Dialysis Patients - Drasko Pavlovic; Hrvojka Tomic Brzac (The Scientific World Journal)
Secondary hyperparathyroidism (SHPT) is one of the most common complications in patients with chronic kidney disease (CKD). Bone and mineral disorders, increased morbidity and mortality are the consequences of SHPT. Therefore, prevention and control of hyperparathyroidism is one of the main objectives in the management of patients with CKD, particularly in dialysis patients.It is well known that SHPT in CKD is not only a state of increased parathyroid hormone (PTH) synthesis and secretion, but more importantly, it is a state of parathyroid gland (PTG) hyperplasia. The serum concentration of intact PTH is the main method used to assess PTG overactivity. Unfortunately, estimating the size and shape of the PTG in SHPT diagnosis, i.e., parathyroid hyperplasia, is still neglected. Among the various procedures, ultrasonography could be the method of choice to detect PTG size and shape because of its simplicity and noninvasiveness. This method can be sufficiently sensitive to distinguish diffuse and nodular hyperplasia.